Strain-specific propagation of variant Creutzfeldt–Jakob disease prions in humanized neural cells - Melissa L. D. Rayner; Parineeta Arora; Jacqueline M. Linehan; Helena Ros; Akin Nihat; Fabio Argentina; Connor Preston; Christian Schmidt; Juan M. Ribes; Peter-Christian Klöhn; Simon Mead; Sebastian Brandner; et al. (Proceedings of the National Academy of Sciences, 2026)
Prions are self-templating assemblies of the host prion protein in which conformational templating encodes heritable “strain” information. Human prion diseases, including Creutzfeldt–Jakob disease (CJD), are rare but uniformly fatal neurodegenerative disorders with established public-health relevance through epidemic and iatrogenic transmission and provide a paradigm for conformational templating in neurodegeneration. Mechanistic analysis of human prion propagation and development of infectivity assays for public health surveillance have been limited by the absence of mammalian cell systems that replicate authentic infectious human prions. Here, we establish a humanized neural cell system that enables propagation of variant CJD (vCJD) prions and reveals that prion replication is constrained by strain-compatible cellular states. The platform was generated using a silencing-followed-by-reconstitution strategy analogous to that used in transgenic mouse models of human prion disease, combined with high-throughput clonal selection. These cells propagate brain-derived vCJD prions and support chronic infection. Prions propagated in vitro transmit disease to humanized transgenic and wild-type mice while preserving defining biochemical and strain-specific neuropathological features, demonstrating faithful propagation. Propagation is strain specific: The cells are permissive to vCJD but refractory to sporadic CJD isolates, indicating that prion replication is constrained by strain-compatible cellular states. These humanized cells enable quantitative detection of infection at high dilution, support systematic genetic manipulation, and are readily adaptable to automation. By overcoming a longstanding barrier of propagating authentic human prions, this platform enables mechanistic dissection of the cellular determinants of prion replication and strain specificity and provides a scalable system for genetic analysis and sensitive detection of infectious human prions.